Northwest History. Alaska. Floods & Flood Control. (1937)
Yukon's Waters Flooding Towns. FAIRBANKS, Alaska, May 18. (/P)—Fresh floods in the Yukon river basin washed through Nenana and Fort Yukon today and drove residents from their homes and places of business. Several feet of water flowed through Fort Yukon, a trading post 150 miles northeast of here at the junction of the Yukon and Porcupine rivers. The residential district of Nenana, 50 miles southwest of here, lay deep in the overflow of the Tanana river which covered the lower part of the town with 14 feet of water at the crest. Water ran through the business section and railroad yards. Estimates of property damage were unavailable at either place. Radiophone reports from Fort Yukon and Nenana mentioned no fatalities.